Distribusi Spasial Lahan Eksploitasi dan Reklamasi Tambang Batubara Menggunakan Data Sentinel-2. - Bagus, Muhammad Ikhwan (JURNAL BUANA, 2025)
This study aims to (1) determine the distribution of land for exploitation and reclamation of coal mines in Sawahlunto City. (2) Knowing the area of ​​land affected by the exploitation and reclamation of coal mines in Sawahlunto City. This type of research is quantitative descriptive research with digital image interpretation methods, field surveys and web programming. The data analysis technique used is Normalized Burn Ratio using image sentinel-2 level 2A and Kernel Density to determine the spatial distribution of land that experiences exploitation and reclamation after coal mining. The results of this study indicate that (1) land that has experienced exploitation and reclamation is highly distributed in the administrative area of ​​Talawi District, Sawahlunto City. (2) The area of ​​land subject to exploitation and reclamation on mining areas in Sawahlunto City in 2020-2021 has increased, which means that in that time span coal mining activities have increased.